Solution of some technical problems in marker and marker locator development - Vestenicky, Peter (Communications - Scientific letters of the University of Zilina, 2004)
This paper gives a short description of selected technical problems and their solutions in development of a marker locator. The principle of underground engineering network equipment marking by markers and principle of marker location is explained. Next, mathematical analysis of signal intensity received from an excited marker and its dependence on distance is described. Moreover, influence of over current induced by lightning into a marker is analyzed and practically measured. These facts were used to increase reliability and lifetime of markers.